(untitled) (Altre Modernità, 2016)
Virginia Woolf is rarely associated with the noir genre. Nevertheless, the themes of crime and of social justice are widely present in her literary production. Particularly, the ideas of crime and of its equal punishment emerge almost obsessively in Mrs Dalloway, where the writer analysed and challenged, in a very modern perspective, the inability of the society of her time to deal with the otherness. The novel, published in 1925, is structured on a double plot, in which Woolf skilfully juxtaposes a socially acceptable society – the summery, middle-class and “sane” London of Clarissa Dalloway – with a darker dimension – the post-war, visionary and “insane” London of Septimus Warren-Smith, a homosexual veteran suffering from shell-shock – where the marginalization of the individual eventually leads to crime. Such a dichotomy allowed Woolf to introduce in her novel themes that were considered taboo at the time, such as the notions of marginality – in this case related to mental illness and homosexuality – and crime. This essay analyses the theme of crime in Mrs Dalloway focusing on the figure of Septimus Warren-Smith, in a comparative perspective and through the autobiographical resources of Woolf’s own diaries and letters.